Pengaruh Pajak Pertambahan Nilai, Digital Marketing, dan Kemudahan Pembayaran terhadap Keputusan Pembelian Online pada E-Commerce Di Kecamatan Rajabasa Kota Bandar Lampung - Amanda Ramadhani; Depita Anggraini; Destia Pentiana (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to analyze the influence of Value Added Tax (VAT), Digital Marketing and Ease of Payment on Online Purchase Decisions on E-Commerce in Rajabasa District, Bandar Lampung City. This study uses a quantitative descriptive approach with primary data obtained through the distribution of questionnaires and processed using SPSS version 26. The sampling technique used the purposive sampling method with a total of 114 respondents. The results of the study show that Value Added Tax and Digital Marketing have a positive and significant effect on online purchase decisions, while Ease of Payment does not have a significant effect. It is recommended for e-commerce players to continue to develop attractive and relevant digital marketing strategies to increase consumer buying interest. In addition, consumers are expected to have a good understanding of the role of Value Added Tax (VAT) in online transactions and utilize information from digital marketing strategies, such as product reviews and promotions, to make wiser and more informed purchasing decisions.